Relationship between shortwave radiation bias over the Southern Ocean and the double‐intertropical convergence zone problem in MRI‐ESM2 - Hideaki Kawai (Wiley, 2021)
Abstract The relationship between improvements in the radiation bias over the Southern Ocean and the alleviation of the double‐intertropical convergence zone (ITCZ) problem in the actual updates of our climate models is investigated. The radiation bias in MRI‐CGCM3 that was used for CMIP5 simulations, particularly over the Southern Ocean, is significantly reduced in MRI‐ESM2 that is used for CMIP6 simulations. Each modification that contributed to the reduction of the radiation bias was progressively reverted to the corresponding older treatment in order to examine their individual impacts on the ITCZ representation. Results show the double‐ITCZ problem worsens almost monotonically when the excessive shortwave insolation over the Southern Ocean increases. The contribution of the atmosphere is about one third of the impact on the total northward energy transport and the corresponding response of the Hadley cell is related to the change in the double‐ITCZ. However, our results also imply that the ITCZ bias cannot be completely resolved by the improvements of radiative flux alone and that there are other causes of the problem.